2021
DOI: 10.3892/etm.2021.9709
|View full text |Cite
|
Sign up to set email alerts
|

Delivery and breastfeeding in pregnant patients with COVID‑19 (Review)

Abstract: COVID-19 infection has rapidly become a global issue that has brought essential changes in the daily life of patients and doctors. The pandemic outbreak represents a significant burden on humankind; yet, life still moves on with approximately 350,000 babies being born every day around the world (UNICEF-2018). Some of these mothers will have other conditions, including COVID-19 infection. As healthcare providers, it is our responsibility to treat all women equal no matter what illness they have and to offer the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Agreeing with our findings, other studies have also shown that the numbers of neonates with 1 and 5 min Apgar scores under 7 were comparable regardless of whether the mothers had COVID-19 ( 26 , 27 ). Moreover, other recent studies found that the percentage of neonates with Apgar scores under 7 was comparable before and during the COVID-19 pandemic ( 7 , 8 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Agreeing with our findings, other studies have also shown that the numbers of neonates with 1 and 5 min Apgar scores under 7 were comparable regardless of whether the mothers had COVID-19 ( 26 , 27 ). Moreover, other recent studies found that the percentage of neonates with Apgar scores under 7 was comparable before and during the COVID-19 pandemic ( 7 , 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…This disagreement about reporting times is evident in the literature; many recent papers only report 5 mins Apgar scores, omitting 1 min scores without providing explanation for their absence ( 7 , 26 , 28 , 33 ). In keeping with the intended testing scheme, however, the vast majority of studies commonly report both 1 and 5 mins scores ( 2 , 24 , 27 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is concluded that all possible care and precautions must be taken, but in a way that preserves as much of the mother-child relationship as possible (DUMIRASCU et al, 2021). Dumitrascu et al (2021) state that direct breastfeeding can favor the transmission of the virus from a mother infected with COVID-19 to her baby (DUMIRASCU et al, 2021), Davanzo et al (2020 contradict themselves saying that, if the mother is asymptomatic or little symptomatic, there should be an effort for the puerperal woman to feed her child directly, as it is not yet clear whether breast milk is capable of making the transmission of the virus viable (DAVANZO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%